Thank you letter from Mr. Blackwell - Blackwell, Richard, author (Colorado State University. Libraries, 1996)
Handwritten letter from Mr. Blackwell to Linda Carlson thanking her and museum colleagues for work on Mr. Blackwell exhibit premiere.
Full name of exhibit event is The Premier Showing of a Collection of Outrageous Designer Gowns by Mr. Blackwell.
Keywords: Fashion -- History; Fashion -- Exhibitions